Mindfulness Based Intervention To Increase Self-Disclosure In Broken Home Children - Bulantika, Siti Zahra; Sa’adah, Sa’adah; Sari, Permata; Mafirja, Sulma (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
The purpose of this study was to examine the effectiveness of mindfulness interventions in increasing self-disclosure in broken home children in MTS N 1 Bandar Lampung. This type of research is an experimental study with the Single Subject Research (SSR) method. The subject is 14 years old grade IX student. The research design used is multiple baseline A1-B-A2. The instrument used is a scale developed from Devito’s theory, which includes five dimensions, namely amount, valence, accuracy/honesty, intention, and intimacy. TheÂ Â studyÂ Â usedÂ Â interraterÂ Â reliabilityÂ Â to displayÂ theÂ reliabilityÂ ofÂ theÂ dataÂ findings.The results showed an effective mindfulness intervention to increase self-disclosure in broken home children. The results of the study provide new knowledge about mindfulness interventions in broken home children to increase self-disclosure so that it can be a reference for other research or individual institutions in the provision or application of mindfulness to help improve self-disclosure.Â